Trends in the interaction of employment and entrepreneurship in the field of culture in the countries of the European union - O. G. Rakauskene; V. V. Velikorossov; S. A. Filin; E. E. Zhussipova; M. K. Seidakhmetov (Экономика: стратегия и практика, 2020)
The purpose of the article is to put forward the problem of the relationship between culture and economic development of the country as a way to consolidate successful economic development in the long term and to assess the impact of culture indicators on economic growth indicators. The article uses the methods of logical research, forecasting, analysis and synthesis based on the system-information approach, the methods of R. Inglehart of the relationship between cultural characteristics and the level of socio-economic development and G. Hofstede of measuring the socio-cultural characteristics of culture. The novelty of the article is justification of the fact that in the conditions of economic instability is of particular importance the proposed approach is based on a study of the economic impact of cultural sector on the growth rate of the economy. It is hypothesized that to achieve socio-economic progress and consolidate the successful development of the country required a close relationship of state and public institutions, culture and applied at the appropriate stage of the standards and their relationship and growth of economic development. The problem of dependence on the previous development of the economy - the «rut effect» and economic statistical indicators in the field of culture in the EU countries are analyzed. Recommendations for changing the sociocultural attitudes of society and its values in the direction of economic development with higher rates of economic growth are proposed. The article makes analytical conclusions about the trends of employment and entrepreneurship in the cultural sphere of the EU countries.